Praktycznie zorientowane ustalanie i optymalizacja ekonomicznej wartości dodanej (EVA) : przykład zastosowania - Gatzki, Christian (Practical-Oriented Finding and Operational Research of EVA : Example of an Application, 2006)
The instruments for measuring value-based company management have been subject of numerous publications. In this regard, the EVA concept itself lies repeatedly at the centre of discussion. The article on hand deals with the approach to value-oriented company management. Thereby, the concept, the application and the goal of EVA are clarified and the calculation is illustrated on the basis of a practical example. As a result, a value-driver-tree for the purpose of cause study and a measures catalog are presented in order to achieve a sustainable increase in Economic Value Added. The declared goal of the paper is to explain the subject clearly and understandable and to present it in a practice-oriented manner based on own experiences.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 183-195